DYNAMICS OF THE DOUBLE-WELL DUFFING SYSTEM - Gregory, Wilson
We consider a Duffing system with double-well potential beam system by F. C. Moon and P. J. Holmes (1979). When there is no forcing, we study the stability of the equilibrium solution with and without small damping. Furthermore, the solution of the unforced system will always bounded. When the system is perturbed with a small periodic forcing, superharmonic and subharmonic cases will appear. We obtain approximations for the solution in the nonharmonic, superharmonic, and subharmonic cases which can provide the dynamics of the solution.